2020
DOI: 10.1039/d0gc01692f
|View full text |Cite
|
Sign up to set email alerts
|

One-pot hydrodeoxygenation (HDO) of lignin monomers to C9 hydrocarbons co-catalysed by Ru/C and Nb2O5

Abstract: A physical mixture of Ru/C and Nb2O5 is an effective catalyst for upgrading lignin monomers under low H2 pressure at 250 °C to a clean cut of hydrocarbon liquid fuels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…3,4 Therefore, the utilization of lignin would not only meet the needs of industrial production and scientific research, but also make an enormous contribution to environmental protection. [5][6][7] However, due to its irregular structure composed of random linkages between monomer components with different oxygenation levels, it is challenging to utilize lignin chemically. 8 Researchers have made many breakthroughs in catalytic methods to break the chemical bonds linking the lignin molecules.…”
Section: Yaxuanmentioning
confidence: 99%
“…3,4 Therefore, the utilization of lignin would not only meet the needs of industrial production and scientific research, but also make an enormous contribution to environmental protection. [5][6][7] However, due to its irregular structure composed of random linkages between monomer components with different oxygenation levels, it is challenging to utilize lignin chemically. 8 Researchers have made many breakthroughs in catalytic methods to break the chemical bonds linking the lignin molecules.…”
Section: Yaxuanmentioning
confidence: 99%
“…19,20 As a relatively cheap noble metal, Ru shows excellent catalytic HDO performance. 21,22 Apart from the active metals, catalyst supports are also crucial for modulating the HDO performance of supported metal catalysts. 23 It was reported that the incompletely coordinated oxophilic Ti 4+ and Zr 4+ cations close to the periphery of active Pd particles were beneficial to the formation of benzene in the HDO of phenol.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, metal sulfides, , metal nitrides, metal phosphides, , and other metal or alloy catalysts have been widely explored in the HDO processes of biomass derivates. Especially, supported noble metals (e.g., Pt, Pd, and Ru) are found to exhibit good catalytic performance in the HDO reactions of guaiacol, vanillin, and other model compounds. , As a relatively cheap noble metal, Ru shows excellent catalytic HDO performance. , Apart from the active metals, catalyst supports are also crucial for modulating the HDO performance of supported metal catalysts . It was reported that the incompletely coordinated oxophilic Ti 4+ and Zr 4+ cations close to the periphery of active Pd particles were beneficial to the formation of benzene in the HDO of phenol .…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of green chemistry and industrial applications, HDO is considered to be the most important and promising method for converting biomass into high-value chemicals . Various metal/carbon catalysts, such as Pd/C, Pt/C, , Ru/C, , and Ni/C, have been widely used for the transformation of biomass . Guo et al developed Ru/C catalysts for the HDO of bio-oil, and the yield of the extracted oil was in the range of 30–65 wt %.…”
Section: Introductionmentioning
confidence: 99%